Appraisal of the Immunization Management in Yogyakarta City, Indonesia: A Case Study - Sulistyawati Sulistyawati; Asma Karimah (Window of Health : Jurnal Kesehatan, 2026)
In 2022, Complete Basic Immunization (CBI) coverage in Yogyakarta City exceeded the provincial target of 95%; however, one health center reported coverage below the city target of 93%, indicating potential challenges in immunization program management. This study aims to evaluate immunization management in Yogyakarta City by assessing input, process, and output components of program implementation. Method: This study employed a qualitative case study approach. Informants were selected using snowball sampling until data saturation was achieved, resulting in six participants from two health centers representing different levels of immunization coverage. Data were collected through in-depth interviews and direct observations, transcribed verbatim, and analyzed using content analysis. Result: Two major themes emerged from the findings. First, human resource capacity was identified as a key challenge, particularly limited compliance with immunization training requirements and insufficient workforce readiness to support service delivery. Second, weaknesses in monitoring practices were observed, as immunization coverage monitoring was implemented less frequently than required by regulations. Despite these operational barriers, both health centers achieved the city's immunization coverage target in 2023. Conclusion: High immunization coverage in Yogyakarta City reflects strong program performance; however, sustaining and improving coverage requires strengthening workforce competency and ensuring routine monitoring implementation. These findings suggest that maintaining immunization outcomes in urban settings depends not only on coverage achievement but also on continuous health system capacity development and program oversight.